Kontribusi Daya Ledak Otot Tungkai dan Koordinasi Mata-Kaki terhadap Kemampuan Shooting Sepakbola PUPUS FC Kabupaten Kepulauan Mentawai - Aldimas Jusinisen Asri; Ridho Bahtra; Andri Gemaini; Ahmad Chaeroni (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
The purpose of this study is to examine the contribution of leg muscle explosive power and foot-eye coordination to the shooting ability of PUPUS FC football players in the Mentawai Islands Regency. The type of research used is quantitative descriptive. The population in this study were all PUPUS FC players, while the sampling technique used total sampling of 22 people. The tests used in this study were the standing broad jump test, the foot-eye coordination test, and the soccer shooting test. The sample in this study was 22 people. From the results of the tests conducted on PUPUS FC soccer players, the results obtained were that there was a contribution between leg muscle explosive power to soccer shooting results of 12.40% and the remaining 87.60% was influenced by other factors, there was a contribution between foot-eye coordination to soccer shooting results of 2.70% and the remaining 97.30% was influenced by other factors, and there was a contribution of leg muscle explosive power and foot-eye coordination to soccer shooting results of 73.10% and the remaining 26.90% was influenced by other factors. The tests used in this study included the standing broad jump test to assess leg muscle explosive power, the foot-eye coordination test to evaluate the players' coordination, and the soccer shooting test to measure their shooting accuracy and effectiveness. These tests are commonly used in sports science to evaluate physical attributes that directly impact athletic performance. The results obtained from the tests indicate that leg muscle explosive power contributed 12.40% to the soccer shooting performance of the players, with the remaining 87.60% influenced by other factors such as technical skill, tactical awareness, and mental readiness. Additionally, foot-eye coordination accounted for 2.70% of the variation in shooting ability, suggesting that while important, it is not the dominant factor in determining shooting success. The remaining 97.30% of the variation could be attributed to other physical, technical, or psychological factors.